The importance and meaning of prayer rituals at the end of life. (14th January 2021) - Anderson, Dean; De Souza, Joanna
Abstract : Death rituals, such as the ritual of prayer, can offer cultural comfort to people who are grieving the loss of their own life or that of another. This article explores the meaning of ritual, how rituals are structured and how prayer rituals are used at the end of life from a cross-cultural perspective. Facing death can be a challenge to a person's sense of identity and their understanding of their world around them, beginning a process of spiritual suffering. Prayer rituals can help maintain a sense of control and identity during this time of crisis, offering comfort, meaning and structure. Despite varying outward appearances, prayer rituals from different cultures follow similar structures that can be deconstructed, allowing nurses to decipher their meaning and deepen the quality of care they provide to the dying person and those left behind.